Visual Framing in Online Photojournalism: Bibliometric and Systematic Review of Media and Social Issues - Melati Budi Srikandi; Naufal Giri Putra; Jonathan Jacob Paul Latupeirissa (Mediator: Jurnal Komunikasi, 2026)
While swift developments in online photojournalism redefine visual framing to alter audience perception, a general synthesis of systemic biases remains uncharted territory. This study fills this gap by mapping the research landscape and conducting a bibliometric and systematic review to identify publication trends and thematic clusters. A systematic literature review based on PRISMA and bibliometric analysis with VOSviewer is used to analyze 163 articles collected from the Scopus database, resulting in 37 articles for the final review. It analyses publication patterns, leading topics and institutions, geographical distributions, and key thematic clusters. Findings show a critical transformation from mono- to multimodal spaces and recurrent worthy versus unworthy´ binary structures in the depiction of refugees that, by virtue of framing them as massified´ people rather than humans, assign non-European others to the status of a non-person. One major contribution is the theoretical integration of infrahumanization into framing literature, highlighting how online platforms embed social prejudice. In practice, the study provides ethical implications for newsrooms to limit the use of dehumanizing imagery. It suggests that further research should examine how algorithmic distribution and AI-generated content affect the visual.